Credit markets for the poor - Bolton, Patrick, 1957-; Rosenthal, Howard, 1939- (Russell Sage, 2005)
"Credit Markets for the Poor demonstrates how weak credit markets are impeding the social and economic mobility of the needy. By detailing the many disadvantages that impoverished people face when seeking to borrow, this new volume highlights a significant national problem and offers solutions for the future."--Jacket